Social Media Marketing as a tool for promoting services and goods on the internet - Iastremska, Olesia; Feshchur, Iryna; Lysytsia, Nadiia; Martynenko, Maryna; Losheniuk, Oksana (Amazonia Investiga, 2023)
This article provides an in-depth analysis of the role of social media as a powerful tool for promoting services and goods on the Internet in the conditions of impressions economy. The authors take a closer look at the role of social media in marketing strategies, its impact on consumers, and the effectiveness of campaigns. The main purpose of the article is to explore various strategies, tactics, and success factors of using social media to support a brand, engage the audience and increase sales. Analyzing various social media marketing strategies, the authors of the article emphasize the importance of creating interesting and meaningful content and engaging with the audience. It reveals the importance of creating a brand identity and supporting it through social media channels. The article also examines the impact of social media on customer purchase, conversion, and loyalty. Among the key success factors of social media marketing, the article identifies the choice of the right platforms, measuring performance, establishing effective interaction with the audience, and analyzing the competitive environment. The authors emphasize the need to combine traditional and digital marketing strategies to achieve the best results. This article is a valuable resource for marketers, entrepreneurs, and marketing professionals looking to increase their online presence and use social media to successfully promote their products and services, taking into account impressions of market subjects. The article provides important tips, strategies, and examples of successful campaigns that contribute to achieving greater success in digital marketing through social media.